The IMPLEMENTATION OF PjBL TO INCREASE STUDENTS' LEARNING ACTIVITY AND MOTIVATION AT SMA MUHAMMADIYAH 3 JEMBER - Arminatul Jannah; Mohamad Zaenal Mahfud; Sawitri Komarayanti (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
This research was conducted with the aim of improving the engagement and motivation in learning biology through the implementation of a project-based learning model, namely Project Based Learning, among students of class XB at SMA Muhammadiyah 3 Jember. Project Based Learning is a contextual learning model that uses projects as a medium, with the expectation of transforming students' learning methods to be more independent by increasing their engagement and motivation. This study employed a classroom action research consisting of three cycles. Data analysis was carried out using quantitative descriptive analysis, and data collection was carried out through observation sheets, questionnaires and documentation. The steps in implementing the Project Based Learning model include determining fundamental questions, designing project plans, creating a schedule for producing the project outcomes, monitoring project engagement and progress, testing the outcomes, and evaluating the learning experience. The results of the study showed that the application of Project Based Learning was able to improve student engagement by 4% and 10%, reaching 62% in cycle 1 and progressively increasing to 66% in cycle 2 and 76% in cycle 3. Student motivation also increased by 4% and 11%, reaching 63% in cycle 1, and further increasing to 67% in cycle 2 and 78% in cycle 3. Therefore, Project Based Learning is recommended for implementation in biology education.